A tale of two forces: simultaneous chemical and acoustic propulsion of bimetallic micromotors. Issue 6 (1st December 2014) - Wang, Wei; Duan, Wentao; Zhang, Zexin; Sun, Mei; Sen, Ayusman; Mallouk, Thomas E.
Abstract : Bimetallic gold–ruthenium microrods are propelled in opposite directions in water by ultrasound and by catalytic decomposition of hydrogen peroxide. Abstract : Bimetallic gold–ruthenium microrods are propelled in opposite directions in water by ultrasound and by catalytic decomposition of hydrogen peroxide. This property was used to effect reversible swarming, to stall and reverse autonomous axial propulsion, and to study the chemically powered movement of acoustically levitated microrods.